2019
DOI: 10.1016/j.ijrobp.2019.06.1761
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Docetaxel plus Cisplatin Versus Cisplatin Concurrent with Radiation in Local Advanced Cervical Cancer: Midterm Results of A Phase III, Multicenter and Randomized Trial

Abstract: To report the physical dosimetry study and preliminary results of a prospective study evaluating 3D-printing template assisted with CT-guidance for 125 I seed brachytherapy to treat recurrent or metastatic gynecological carcinoma. Materials/Methods: In this retrospective study, with median follow-up of 10 months for all patients, 95 patients were enrolled and analyzed; inclusion criteria were Karnofsky performance status 60 to 100, expected overall survival >3 months, patients were pathologically or radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…When comparing to CCRT, the efficiency of CCRT followed by ACT is still controversial and needs further research. Zhang's [11] results in 2019 revealed that statistical difference was not found in OS and PFS among CCRT followed by ACT and CCRT, the same results were also reported in the results of Chatterjee [27] and Cheng [12]. However, Chen's [10] results indicated that CCRT followed by ACT was associated with better PFS.…”
Section: Discussionmentioning
confidence: 70%
“…When comparing to CCRT, the efficiency of CCRT followed by ACT is still controversial and needs further research. Zhang's [11] results in 2019 revealed that statistical difference was not found in OS and PFS among CCRT followed by ACT and CCRT, the same results were also reported in the results of Chatterjee [27] and Cheng [12]. However, Chen's [10] results indicated that CCRT followed by ACT was associated with better PFS.…”
Section: Discussionmentioning
confidence: 70%